Frontal Mixed Dermoid Tumor with Osteoma in an Infant: A Rare Case with Cranioplasty and Complete Recovery - Sarkar, Saumik; Dey, Avijit; Saha, Shuvro; Sarkar, Saumitra (Journal of Shaheed Suhrawardy Medical College, 2025)
We present a rare case of a 6-month-old female infant with a progressively enlarging, mildly painful swelling on the forehead over three months. Imaging studies revealed a mixed-density lesion extending externally through a frontal skull defect. The patient underwent surgical excision of the mass along with cranioplasty using titanium mesh. Histopathology confirmed a mixed dermoid tumor with an osteoma component. The patient achieved full neurological recovery postoperatively. This case underscores the importance of early imaging and timely surgical intervention in congenital cranial masses. J Shaheed Suhrawardy Med Coll 2024; 16(1): 64-66